2015
DOI: 10.1080/19393210.2014.1001795
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary drug residues in domestic and imported foods of animal origin in the Republic of Korea

Abstract: The Korean National Residue Programme comprises three different approaches for evaluating domestic and imported foods of animal origin: monitoring, surveillance/enforcement and an exploratory test programme. Monitoring and surveillance/enforcement testing programmes are routinely implemented by 17 Provincial Veterinary Services for domestic products and regional offices of the Animal and Plant Quarantine Agency (QIA) for imported products. The exploratory project conducted at QIA headquarters is designed to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Concentration of active ingredient is the most important characteristic of a drug product, as the amount of active ingredient allows to determine the intensities of treatment and toxicity of that particular drug. Moreover, the noncompliance rates of veterinary medicines are also pertaining in the elevation of contamination and drugs residues in the food products of animal origin [ 14 , 15 ]. The NPMS assessment was initiated in 1964 for the quality control of OCD which are in distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of active ingredient is the most important characteristic of a drug product, as the amount of active ingredient allows to determine the intensities of treatment and toxicity of that particular drug. Moreover, the noncompliance rates of veterinary medicines are also pertaining in the elevation of contamination and drugs residues in the food products of animal origin [ 14 , 15 ]. The NPMS assessment was initiated in 1964 for the quality control of OCD which are in distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Gentili et al found no presence of PBZ in meat samples collected random from the Italian market. On the contrary, van Pamel et al found levels of 2 μg/kg for PBZ and 3.3 and 4.6 μg/kg for OXPBZ in horse meat samples, while Kang et al detected only 1 positive cattle liver sample at concentrations of 247 μg/kg and 15 μg/kg for PBZ and OXPBZ, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The APQA implements a post‐production quality control system of collection and inspection of circulating veterinary drugs in order to prevent the production and distribution of low‐quality drugs (MAFRA (Ministry of Agriculture, Food, and Rural Affairs), 2017b; Kang et al., 2015; Kang, et al., 2017). The products included in these inspections are mostly those with high volumes of sales or those that have consistently shown high rates of noncompliance.…”
Section: Discussionmentioning
confidence: 99%